Implementación de una empresa de servicios variados para los hogares “House Services” - Martínez Escobar, Diana Carolina (2020)
This project is the result of an entrepreneurial initiative that seeks to exploit the benefits of virtual commerce based on service platforms. The aforementioned is due to the fact that today in homes there is no time to give immediate solutions to a series of problems that arise and in most cases they are fortuitous. As a solution alternative to this problem, this project called House Services is designed, which is aimed at providing comprehensive solutions to exclusive problems in the home, whether with electrical appliances, paint, masonry, plumbing, locksmith, carpentry, gardening, among others. The business idea has been validated with the Canvas methodology and its target market context is the City of Babahoyo. Feasibility analyzes are positive and stimulate the action to take advantage of this business opportunity